Audit of catering network state in Kharkiv city - Anisimov, Genadiy; Zhukov, Yevhenii; Lipovoy, Denis (Technology audit and production reserves, 2017)
The object of research is the network of catering enterprises in Kharkiv (Ukraine). One of the most problematic places is the forecast of the prospects for managing existing and newly created catering enterprises. From the organizational and technical point of view, this problem is related to the uncertainty of the types of enterprises and the capacity of their trading halls. The study uses statistical information on the state of the city network of catering enterprises for the period 2013–2016. The main organizational and technical indicators of the audit object are stratified according to the types of enterprises and the capacity of their trading halls. Tabulation and graphical representation of stratified data make it possible to identify trends in the development of the audit object. It is established that the urban network is characterized by a constant increase in the number of enterprises and an increase in the total capacity. At the same time, the integral share of the capacity of enterprises selling food and drinks to consumers, united by professional features, is 49.4 %. This is due to the fact that at the moment the Kharkiv food network is equally directed both to the provision of food services during working hours and to the provision of services outside of working hours. At the same time, the average capacity of catering enterprises is decreasing. The most common types of catering enterprises are cafes and bars with small shopping halls (on average 37 and 21 places respectively). This is due to the fact that the peculiarity of such types of enterprises is the availability of small trading halls, oriented to creating a cozy atmosphere during leisure. Due to the revealed tendencies, it is possible to make effective organizational decisions when designing new and reconstructing existing catering enterprises. This can create competitive advantages both for enterprises within the framework of network structures, and for individual catering enterprises.